If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + -9)(9x + 3) = 0 Reorder the terms: (-9 + 8x)(9x + 3) = 0 Reorder the terms: (-9 + 8x)(3 + 9x) = 0 Multiply (-9 + 8x) * (3 + 9x) (-9(3 + 9x) + 8x * (3 + 9x)) = 0 ((3 * -9 + 9x * -9) + 8x * (3 + 9x)) = 0 ((-27 + -81x) + 8x * (3 + 9x)) = 0 (-27 + -81x + (3 * 8x + 9x * 8x)) = 0 (-27 + -81x + (24x + 72x2)) = 0 Combine like terms: -81x + 24x = -57x (-27 + -57x + 72x2) = 0 Solving -27 + -57x + 72x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-9 + -19x + 24x2) = 0 Factor a trinomial. 3((-1 + -3x)(9 + -8x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-1 + -3x)' equal to zero and attempt to solve: Simplifying -1 + -3x = 0 Solving -1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = 0 + 1 -3x = 0 + 1 Combine like terms: 0 + 1 = 1 -3x = 1 Divide each side by '-3'. x = -0.3333333333 Simplifying x = -0.3333333333Subproblem 2
Set the factor '(9 + -8x)' equal to zero and attempt to solve: Simplifying 9 + -8x = 0 Solving 9 + -8x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -8x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -8x = 0 + -9 -8x = 0 + -9 Combine like terms: 0 + -9 = -9 -8x = -9 Divide each side by '-8'. x = 1.125 Simplifying x = 1.125Solution
x = {-0.3333333333, 1.125}
| 5(3-(-2))= | | 2x^2+8x-42=0 | | 8(x+3)-18= | | 10x^2=90 | | 2(n)=16 | | 14-.125w=.75w-21 | | v^2+4x-21=0 | | v^2+v-2=0 | | 50a^3-2ab^2=0 | | x^2+2=y | | n+16=19 | | 2n-9n=80 | | 2(-2)+3(3)= | | 12x-13= | | 7(z-5)+5z-4= | | 6x+5=86-7x | | 3x^2-22x=-24 | | .02(8.5y-2)=0.3 | | 80=9(2x-17) | | -2x^2+288=0 | | 3x=x+54 | | 5+10x=113+6 | | a+10a+16=0 | | 0=-y^2+6y-3 | | 8x^2-288=0 | | a+1=3 | | -x^2+121=0 | | -x^2-121=0 | | 50=48x-16x^2 | | X^3+x^2-42x=0 | | 6(9c-1)-12=52c+6 | | 5a*2+5ab= |